Beyond Neoclassical Economics: The Impact of Religion on the Economic Disparity Between Georgia and Estonia - Mgaloblishvili Anastasia (Baltic Journal of European studies, 2018)
The aim of this article is to examine the impact religion has had on the post-Soviet economic development of Georgia and Estonia. The role of religion in economic development has been neglected in the field of social sciences, in which political and economic theories dominate. Considering the difference in the religiosity of the two countries—Georgia is one of the most religious countries in Europe while Estonia is the most atheist—religion will be incorporated as a factor that could have directly or indirectly impacted the post-Soviet development of the two countries. By studying the relationship of the church and the state in the two countries and the population’s economic attitudes that may have been influenced by their religiosity, this paper will conclude that religion can be considered a contributing factor in the economic divergence between Estonia and Georgia. The article’s overall findings will suggest that the practice of Eastern Orthodoxy in Georgia impedes the development of good governance and a free market economy, whereas the opposite holds for Protestantism or atheism in Estonia.